IMPLEMENTASI LAYANAN BIMBINGAN DAN KONSELINGUNTUK PENCEGAHAN MASALAH BELAJAR PESERTA DIDIK DALAM STUDI PADA MADRASAH ALIYAH NEGERI 2 PAREPARE - HAMDANAH, HJ. HAMDANAH (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2014)
This study is a descriptive correlational survey with a quantitative approach. To obtain the data used questionnaire technique, observation, and documentation. Analysis of the data were descriptive and inferential statistical analysis. Descriptive analysis is done by describing the research variables through the average value, standard deviation, or standard deviation, median, mode and frequency distribution table. Medium-the inferential statistical techniques used are double correlation and ANOVA. The results showed: 1) Implementation and support services BK subject teachers against BK services for the prevention of problems of learners are in the category of being and the prevention of learning problems are still the medium category. 2) Implementation guidance signifcantly correlated with the prevention of learning problems of learners. 3) Support subject teachers who did not have a signifcant correlation with the prevention of learning problems of learners. 4) There is a signifcant correlation between the implementation of the guidance and support services subject teachers together with the prevention of learning problems of learners. The magnitude of the effective contribution of the implementation of the guidance and support services subject teachers together to study the problem of prevention is 11.90%, 88.10% in the sense that the other is inï¬uenced by other variables that are not observed in this study. The relative contribution of each variable is SR = 92.68% X1, X2 SR% = 7.32% and the effective contribution of each variable is SE% 11:03 and SE X1 = X2 = 0.87%. Thus, prevention of learning problems of learners can be increased by improving the implementation and support services BK subject teachers against BK services